Development and validation of RP-HPLC method for the determination of Darifenacin Hydrobromide in bulk drug and pharmaceutical dosage form - Acharya, Ankit; Satish, N.K.; Manoj, L.; Chitti, Renukaradhya (Kathmandu University Journal of Science, Engineering and Technology, 2018)
The main objective of present study is to develop and validate a new, simple, precise and accurate RP-HPLC method for the determination of Darifenacin Hydrobromide (DFH) in bulk and pharmaceutical dosage forms. The separation and quantification of the drug was achieved on a RP C18 column (250×4.6mm, 5μm) using a mobile phase of acetonitrile: buffer (50:50), pH 3.0 ± 0.2 at a flow rate of 1 mL/min with detection of analyte at 287 nm. The separation was achieved with in 4.0 ± 0.3 min. The method showed good linearity in the range of 10-100 μg/mL. The intra and inter day RSD ranged from 0.20-0.58%. The recovery (mean ± SD) of low, medium and high concentrations were 98.50 ± 0.20, 100.27 ± 0.15 and 100.90 ± 0.09 respectively. The limit of detection and limit of quantification were 0.31 and 0.61 μg/mL, respectively. It can be concluded that the present method could be superior over the methods which were reported earlier. Kathmandu University Journal of Science, Engineering and TechnologyVol. 13, No. 1, 2017, Page: 36-44